Flow Diversion for Intracranial Aneurysms Beyond the Circle of Willis - Yu, Jinlu; Lv, Xianli (Frontiers in Neurology, 2021)
Background: Few reports have shown the therapeutic outcomes of flow diversion (FD) for intracranial aneurysms beyond the circle of Willis, and the efficacy of this technique remains unclear. Materials and methods: A retrospective study was performed on 22 consecutive patients, diagnosed with intracranial aneurysms beyond the circle of Willis, and treated with pipeline embolization device (PED) (Medtronic, Irvine, California, USA) between January 2015 and December 2019. Result: The 22 patients were between 16 and 66 years old (mean 44.5 ± 12.7 years), and six patients were male (27.3%, 6/22). Twenty-two patients had 23 aneurysms. The 23 aneurysms were 3–25 mm in diameter (12.2 ± 7.1 mm on average). The diameter of the parent artery was 1.3–3.0 mm (2.0 ± 0.6 mm on average). The 23 aneurysms were located as follows: 17 (73.9%, 17/23) were in the anterior circulation, and 6 (26.1%, 6/23) were in the posterior circulation. PED deployment was technically successful in all cases. Two overlapping PEDs were used to cover the aneurysm neck in 3 cases. One PED was used to overlap the two tandem P1 and P2 aneurysms. Other cases were treated with single PED. Coil assistance was used to treat 7 aneurysms, including 4 recurrent aneurysms and 3 new cases requiring coiling assistance during PED deployment. There were no cases of complications during PED deployment. All patients were available at the follow-up (mean, 10.9 ± 11.4 months). All patients presented with a modified Rankin Score (mRS) of 0. During angiographic follow-up, complete embolization was observed in 22 aneurysms in 21 patients, and one patient had subtotal embolization with the prolongation of stasis in the arterial phase. Conclusion: PED deployment for intracranial aneurysms beyond the circle of Willis is feasible and effective, with high rates of aneurysm occlusion.